Pengaruh Return On Asset, Return On Equity, dan Earning Per Share Terhadap Harga Saham Pada Perusahaan Manufaktur Sektor Farmasi di Bursa Efek Indonesia - Irmansyah Irmansyah; Nita Fitria; Nofrivul Nofrivul; Sri Madona Saleh (Universitas Islam Negeri Mahmud Yunus Batusangkar, 2024)
This research aims to determine the effect of Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS) on share prices in pharmaceutical sector manufacturing companies listed on the Indonesia Stock Exchange from 2018 to 2022. This research uses the method quantitative with secondary data sources. This research uses the analysis method T Test (partial), F Test (simultaneous), and company multiple linear regression. The analysis tool used is Eviews 10. The results of this research are that the variables Return On Assets (ROA) and Return On Equity (ROE) have no influence on share prices in pharmaceutical sector manufacturing companies on the Indonesian Stock Exchange in 2018-2022. The Earning Per Share (EPS) variable has an influence on share prices in pharmaceutical sector manufacturing companies on the Indonesian Stock Exchange in 2018-2022. The variables Return On Assets (ROA), Return On Equity (ROE), and Earning Per Share (EPS) influence share prices in pharmaceutical sector manufacturing companies on the Indonesian Stock Exchange in 2018-2022